2015
DOI: 10.1155/2015/523851
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Immediate Effect of Auricular Acupuncture on Pain and Electromyographic Activity of the Upper Trapezius Muscle in Patients with Nonspecific Neck Pain: A Randomized, Single-Blinded, Sham-Controlled, Crossover Study

Abstract: Background. The aim of the present study was to assess the immediate effects of auricular acupuncture (AA) on the electromyographic (EMG) activity of the upper trapezius muscle and pain in nonspecific neck pain (NS-NP) patients. Twelve patients with NS-NP (NS-NP group) and 12 healthy subjects (HS Group) were enrolled in a randomized, single-blinded, crossover study. Each subject received a single session of AA and sham AA (SAA). Surface EMG activity was measured in the upper trapezius muscle at different “step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 35 publications
0
21
0
1
Order By: Relevance
“…A total of 930 individuals participated in the selected studies, with age varying from 18 to 90 years of age, whereas 462 were in the groups that received auricular acupuncture, and 468 were in the control groups. All participants presented chronic pain conditions (8) , whereas the lumbar spine was the most affected region (n=10), (17)(18)(19)(20)(21)(22)(23)(24)(25)(26) followed by the cervical region (n=3) (27)(28)(29) , and the dorsal region as a whole (n=2) (30)(31) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 930 individuals participated in the selected studies, with age varying from 18 to 90 years of age, whereas 462 were in the groups that received auricular acupuncture, and 468 were in the control groups. All participants presented chronic pain conditions (8) , whereas the lumbar spine was the most affected region (n=10), (17)(18)(19)(20)(21)(22)(23)(24)(25)(26) followed by the cervical region (n=3) (27)(28)(29) , and the dorsal region as a whole (n=2) (30)(31) .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the RCT methodological quality, all studies reported using the random sequence generation method, and in just three this process was not appropriate (23)(24)(25) . In two RCT (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) there was no description of masking, and in other two (24)(25) this masking was considered inadequate. There was no description of loss to follow-up in three RCT (20,23,27) .…”
Section: Continue…mentioning
confidence: 99%
See 1 more Smart Citation
“…Os estudos que abordaram a auriculoterapia o fizeram de formas diferentes. No estudo de Silva et al 18 o tratamento foi aplicado nos pontos "cintura escapular" e "ombros", com o objetivo de avaliar a dor cervical dos pacientes e ainda verificar a resposta eletromiográfica do músculo trapézio superior à aplicação da auriculoterapia. No estudo de Chassot et al 8 foram utilizados os pontos shen men e relaxamento muscular de forma complementar ao foco principal do estudo, que era o efeito da eletroterapia na região cervical e seus efeitos na liberação do marcador BDNF.…”
Section: Discussionunclassified
“…The literature presents very convincing scientific evidence on the control of chronic back pain using separately Chinese (Moura et al, 2018;Yeh et al, 2015Yeh et al, , 2014 and French EA approaches (Sator-Katzenschlager et al, 2004, 2003Silva et al, 2015). Although studies clearly based on the Chinese EA bring more accurate results in relation to those following the French line, difficulty is still found in distinguishing which line of treatment is used in the selection of auricular points, since this information is not always explicit in methodology.…”
Section: Introductionmentioning
confidence: 99%